Asuhan Keperawatan Pada Bayi BBLR Yang Terpasang CPAP Dengan Penerapan Terapi Nesting dan Posisi Pronasi Terhadap Status Hemodinamik - Dewi Sumiyati; Ria Setia Sari (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
Background: BBLR refers to a disruption in the respiratory system of a baby caused by unstable physiological functions, including temperature, pulse, and oxygen saturation. One strategy for managing the condition is the implementation of continuous positive airway pressure (CPAP), a non-invasive technique. Developmental care further reinforces the efficacy of CPAP. One specific effort in providing developmental care is to modify the position of newborns to a comfortable state via nesting. Objective: This scientific paper seeks to examine the effects of nesting therapy and pronation posture on the hemodynamic status of low weight newborns in the BBLR population. CPAP is installed in the Perinatology Room of RSUD Kabupaten Tangerang. Method: Provision of Nursing Care Intervention and innovation in the application of nesting and pronation position against hemodynamics. Results: Based on case studies in managed patients, there were changes in hemodynamic status such as pulse, breathing and temperature in patients before and after treatment.